The Effect of Toothbrushing Duration on Nickel Chromium Alloy Wear - Sri Budi Barunawati; Siti Sunarintyas; Rini Dharmastiti (The Indonesian Journal of Dental Research, 2012)
Nickel-chromium alloy is a preferred material for fixed partial denture due to its low cost as well as good physical and mechanical properties. Tooth brushing using toothpaste produces abrasion on restoration, especially in a long period. This study aimed to observe the effect of toothbrushing duration on the wear of nickel-chromium alloy. Twenty four specimens of nickel-chromium alloy (Metal 4all, Ivoclar, USA) in 30X15X1mm3 dimension were treated using tooth brushing simulation machine (wear test machine, pin on plate unidirectional movement type) and toothpaste (modification of Balsam formula). The brushing durations were 30.9, 77.25, 123.6, and 154.5 hoursas the simulation of 2, 5, 8, and 10 years tooth brushing. Surface roughness and weight difference as abrasion indicator were measured and analyzed using one-way ANOVA followed by LSD test. Tooth brushing duration of 2, 5, 8, and 10 years increased nickel-chromium alloy surface roughness (Ra) by 0.16, 0.39, 0.43, and 0.56µm with weight loss of 8%, 15%, 23%, and 32 %, respectively. These differences were statistically significant (p <0.05). The result of LSD test showed a significant effect (p <0.05) between groups of toothbrushing duration. The increase of surface roughness affects the increase of wear volume of nickel-chromium alloy indicated by R = 0.11 for brushing duration of 2, 5, 8, and 10 years. The conclusion of this study was 10 years tooth brushing promoted wear on nickelchromium alloy, whichwas indicated by the increase in surface roughness and weight loss.